Thailand's State Gastro Diplomacy Policy Is an Effort to Maintain The Existence Of Tourism In The Face Of Globalization - Yuniningsih, Tri; Larasati, Endang; Suwitri, Sri; Hanura, Marten; Hidayati, Rizki (Iapa Proceedings Conference, 2024)
To increase foreign tourist visits, one of the policies implemented by Thailand is to have a gastro diplomacy policy. This policy is related to efforts to attract tourists to visit a country through the introduction of culture, art, education and culinary. The focus of this study is on the introduction of superior cuisine owned by Thailand. This study aims to analyze the gastro diplomacy policy implemented by the Thai government by introducing culinary and identifying inhibiting factors. This study uses a literature study approach. The study results show that the Thai Government has succeeded in developing culinary by launching various programs, namely Kitchen in the World, culinary events, cooperation with domestic media, the private sector and other supporting actors. However, there are various obstacles in implementing the gastro diplomacy policy, namely negative image, globalization, lack of political support, tourism threats, political controversy, standardization and quality, infrastructure and logistics, human resources, government regulations and policies, climate change and food security. Therefore, the Thai Government must make various efforts to overcome obstacles to gastro diplomacy, including strengthening education and training, increasing public-private cooperation, campaigning for storytelling promotion, developing derivative products, and utilizing digitalization.